DETERMINANTS OF CREDIT RISK IN THE NIGERIAN BANKING INDUSTRY - Ebenezer, Ariyibi Mayowa; Opubor, Efemena Emily; Enitan, Olowofela Olusola (Journal of Management Small and Medium Enterprises (SMEs), 2025)
The deposit money banks are faced with the problem of credit risk, which occurs from their intermediary role in the economy, which is channeling customers’ deposits from the surplus sector to the deficit/productive sector to improve their performance and stimulate financial stability and growth. It is imperative to examine the internal and external factors that influence the credit risk component of the deposit money banks in Nigeria. This study examines the determinants of credit risk in the Nigerian banking industry. The secondary data was sourced from twelve deposit money banks listed on the Nigerian Stock Exchange Group from 2019 to 2023. The static regression analysis was employed to determine the inference of the objective. The findings from the fixed effect model revealed that board size, operating efficiency, bank size, gross domestic product growth rate, and unemployment rate have a significant effect on the non-performing loan ratio, while return on assets, board independence, loan-to-deposit ratio, debt-to-equity ratio, loan-to-total asset ratio, and inflation rate have an insignificant effect on the non-performing loan ratio. Therefore, it is recommended that deposit money banks in Nigeria integrate internal governance enhancements with macroeconomic stability, which is essential for effectively managing non-performing loans in Nigerian banks. Collaborative efforts between banks, regulators, and policymakers are critical to achieving sustainable credit risk management. Keywords: Credit Risk; Profitability; Liquidity; Corporate Governance; Macroeconomic